Effectiveness of the Japanese DOLOPLUS‐2: a pain assessment scale for patients with moderate‐to‐severe dementia. Issue 5 (12th January 2016) - Ando, Chiaki; Ito, Yoshinori; Amemiya, Shimon; Tamura, Kyoko; Kako, Ken; Tsuzura, Satoko; Yoshida, Ryoichi; Hishinuma, Michiko
Abstract: Background: This study aimed to assess whether the Japanese DOLOPLUS‐2 scale could effectively identify pain in elderly individuals with moderate‐to‐severe dementia. Methods: This study used a pre‐test/post‐test design with purposive sampling to select an experimental group and a historical control group. The inclusion criteria were a Functional Assessment Staging score of 5 or 6, a diagnosis of an orthopaedic disease that typically involves pain, the ability to say 'I am currently in pain' (to prevent medication errors), and a total DOLOPLUS‐2 scale score ≥5 at the first pain assessment. In the experimental group ( n = 19), each patient was assessed by the DOLOPLUS‐2 scale at 2PM and 9PM each day for 5 days. If a patient's total score was ≥5, analgesics were prescribed and the patient was re‐assessed approximately 3 hours later. In the control group ( n = 20), data were collected from medical records over a 1‐year period, and we matched the characteristics of the control group to that of the experimental group. We also reviewed nursing records to determine the number of times analgesics had been administered over the 5 days after the nurses had first recorded that the patient had experienced pain. Results: Among the 19 patients in the experimental group, 15 received pain medication because of a total pain score ≥5. Before treatment, their mean DOLOPLUS‐2 scale score was 7.5 ± 3.2, and their score significantly decreased to 2.9 ± 2.1 (P < 0.001) after treatment. The experimental group also received significantly more treatments with analgesic medication than the control group (χ 2 = 16.033, P < 0.001, φ = 0.641). Conclusion: This study's findings suggested that the Japanese DOLOPLUS‐2 scale could adequately identify pain in elderly individuals with moderate‐to‐severe dementia.